Boutiques: a flexible framework to integrate command-line applications in computing platforms. Issue 5 (23rd March 2018) - Glatard, Tristan; Kiar, Gregory; Aumentado-Armstrong, Tristan; Beck, Natacha; Bellec, Pierre; Bernard, Rémi; Bonnet, Axel; Brown, Shawn T; Camarasu-Pop, Sorina; Cervenansky, Frédéric; Das, Samir; Ferreira da Silva, Rafael; et al.
Abstract: We present Boutiques, a system to automatically publish, integrate, and execute command-line applications across computational platforms. Boutiques applications are installed through software containers described in a rich and flexible JSON language. A set of core tools facilitates the construction, validation, import, execution, and publishing of applications. Boutiques is currently supported by several distinct virtual research platforms, and it has been used to describe dozens of applications in the neuroinformatics domain. We expect Boutiques to improve the quality of application integration in computational platforms, to reduce redundancy of effort, to contribute to computational reproducibility, and to foster Open Science.